2020
DOI: 10.3390/met10101341
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation and Dynamic Recrystallization Behavior of CoCrNi and (CoCrNi)94Ti3Al3 Medium Entropy Alloys

Abstract: The CoCrNi and precipitate-hardened (CoCrNi)94Ti3Al3 medium entropy alloys (MEAs) have attracted much attention, due to their exceptional mechanical properties, whereas the hot deformation characteristics have not been revealed. In the present study, we investigated the dynamic recrystallization behavior and microstructure evolutions of the two MEAs hot-compressed at single-phase temperatures. The constitutive equation was obtained, and microstructures were observed. Discontinuous dynamic recrystallization act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…The apparent activation energy of the Cantor HEA is close to that of the diffusion of Ni in the alloy, and the dislocation climb determines the steady-state deformation [25][26][27][28][29][30][31][32]. Even though the DRX behaviors of CoCrNi MEA and the novel Co-rich TRIP HEA were investigated in our previous studies [14,24], the influence of interstitial atoms such as C and N on hot-deformation and grain structure evolution have not been clarified.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The apparent activation energy of the Cantor HEA is close to that of the diffusion of Ni in the alloy, and the dislocation climb determines the steady-state deformation [25][26][27][28][29][30][31][32]. Even though the DRX behaviors of CoCrNi MEA and the novel Co-rich TRIP HEA were investigated in our previous studies [14,24], the influence of interstitial atoms such as C and N on hot-deformation and grain structure evolution have not been clarified.…”
Section: Introductionmentioning
confidence: 95%
“…One of the more promising strategies is to introduce interstitial non-metal atoms (C, N, O) into the solid solutions of the metals, benefiting from the interstitial solid-solution strengthening and/or the short-range order/ordered complexes [13][14][15][16][17]. Moreover, the yield strength could also be further enhanced by reducing the grain size, wherein fine grains result in a high yield strength, which is known as the Hall-Petch relation [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the deformation behavior of the CoCrFeMnNi HEA and the CoCrNi medium entropy alloy at a temperature higher than 1073 K was investigated, and the constitutive relationships between the flow stress, strain, strain rate, and temperature were clarified [ 17 , 18 , 19 , 20 , 21 , 22 ]. Research reported that the evolution of grain structure is accompanied by the discontinuous dynamic recrystallization (dDRX), in which the newly recrystallized grains were referred to the form at the original grain boundaries (GBs) [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%